Impact of Facebook, TikTokand Instagram advertising onthe Arlington VA community - Melo Flórez, Paula; Vargas Hernández, César Asdraldo (Ingeniería Solidaria, 2023)
This paper is a product of the research about “Advertisement impact in Facebook, Tik Tok and Instagram in Arlington Virginia community” developed in the Francisco Jose de Caldas University in 2022.Introduction: Over time, generations have been changing and developing new consumer trends. In the same way, companies have been evolving to be able to adapt to the different trends to reach the target audience using diverse ways of advertising.Method: This paper makes use of databases such as Scopus, Google Scholar, Index-K as sources of information to guide the research of social media use. Using statistics and articles we determine the main aspects that guide the behavior and the use of the different social media platforms in the different age groups.Results: This Paper shows that depending on the age group the use of social media is different; the youngest users prefer platforms where they can share videos or images.Conclusions: As people grow, people are more attracted by platforms like Facebook where they can find social interaction, information and they can share different type of content.Limitation: This paper is focused on people that live in Arlington a small city in the state of Virginia. The information found can be a basis for analyzing users' behaviors on different platforms.
Keywords: advertising; Facebook; Instagram; Tik Tok; trends; social networks